Fisher–Shannon Analysis of Sentinel 1 Time Series from 2015 to 2023: Revealing the Impact of Toumeyella Parvicornis Infection in a Pilot Site of Central Italy - Luciano Telesca; Nicodemo Abate; Michele Lovallo; Rosa Lasaponara (Entropy)
This study investigates the capability of Sentinel-1 (S1) SAR time series to identify vegetation sites affected by pest infestations. For this purpose, the statistical method of the Fisher–Shannon analysis was employed to discern infected from unifected forest trees. The analysis was performed on a case study (Castel Porziano) located in the urban and peri-urban areas of Rome (Italy), which have been significantly impacted by Toumeyella parvicornis (TP) in recent years. For comparison, the area of Follonica (Italy), which has not yet been affected by this insect, was also analyzed. Two polarizations (VV and VH) and two orbit types (Ascending and Descending) were analyzed. The results, supported by Receiver Operating Characteristic (ROC) analysis, demonstrated that VH polarization in the Descending orbit provided the best performance in identifying TP-infected sites.